Analysis Of Electrostatic Precipitator (Esp) Performance Based On Changes In Reference Voltage And Temperature In The Coal Boiler At Pt. Chandra Asri So Puloampel - Mahendra, Adit Yuda; Subairi, Subairi; Kartika Sari, Resi Dwi Jayanti (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to gain an in-depth understanding of various factors that influence the performance of electrostatic precipitator (ESP) systems in industrial environments. An experimental method with a quantitative approach was used to analyze the effects of reference voltage and temperature on ESP performance. The research process involved data collection through observation, efficiency calculations using the Deutch-Anderson equation, and direct system testing. A monitoring system based on Arduino Uno WiFi R3 and ESP8266 was designed to track voltage, current, and sparking activity in real-time via the Blynk application. Flowcharts were used to illustrate the stages of analysis and the development of the monitoring tool as part of the overall research process. The findings indicate that the performance of the electrostatic precipitator (ESP) is significantly influenced by the settings of reference voltage and current, temperature, and compartment environmental conditions. Efficiency reached only 75% when the feedback voltage was 42kV with a current of 100mA, highlighting the need for simultaneous adjustment of voltage and current to achieve the optimal 99.5% efficiency. The highest resistance value of 9.13 GΩ at a temperature of 69.4°C demonstrates the importance of maintaining cleanliness and humidity to reduce the risk of sparking. The monitoring system based on Arduino Uno WiFi R3 and ESP8266 successfully displayed real-time data via Blynk, despite an error margin of ±6%. Additionally, the safety indicator system functioned effectively in detecting disturbances and supporting the safe operation of the ESP.